Sum-Power Minimization in Multiuser Single-DF-Relay Networks with Direct Links - Shiguo Wang; Haixia Peng; Xianru Liu (International Journal of Distributed Sensor Networks)
Forming cooperation through relay's assistance is a promising method to realize green communication by reducing transmission power. In this paper, for multiuser single-DF-relay wireless networks with direct links, the optimal power allocation strategy that minimizes system-sum-power consumption is investigated. Based on the principle that minimizing system-sum-power consumption is equivalent to maximizing system energy efficiency, users are classified into two parts after comparing the channel gains between source-destination link and relay-destination link. The optimal power allocation strategy of one part is determined directly, and minimizing the system-sum-power consumption of the other part is converted into minimizing source-sum-power consumption, which can be solved easily through Karush-Kuhn-Tucker (KKT) condition. Through numerical simulations, we further justified the effectiveness of our scheme compared to existing works.